2008
DOI: 10.1093/aob/mcn093
|View full text |Cite
|
Sign up to set email alerts
|

C4 photosynthesis and water stress

Abstract: It is suggested that there is a limited capacity for photorespiration or the Mehler reaction to act as significant alternative electron sinks under water stress in C(4) photosynthesis. This may explain why C(4) photosynthesis is equally or even more sensitive to water stress than its C(3) counterpart in spite of the greater capacity and water use efficiency of the C(4) photosynthetic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
299
1
29

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(345 citation statements)
references
References 54 publications
16
299
1
29
Order By: Relevance
“…This suggested that C 4 plants have higher carbon sequestration under drought conditions. These results are consistent with previous research that C 4 plants have an advantages in Pn in drought conditions compared with C 3 plants [30,44,45] because the C 4 CO 2 -concentrating mechanism offers C 4 photosynthesis a greater buffering capacity against CO 2 shortages due to partial stomatal closure under water stress [46]. However, drought increased C 3 WUE overall, but tended to decrease C 4 WUE (Figure 1).…”
Section: Photosynthetic Pathwayssupporting
confidence: 92%
“…This suggested that C 4 plants have higher carbon sequestration under drought conditions. These results are consistent with previous research that C 4 plants have an advantages in Pn in drought conditions compared with C 3 plants [30,44,45] because the C 4 CO 2 -concentrating mechanism offers C 4 photosynthesis a greater buffering capacity against CO 2 shortages due to partial stomatal closure under water stress [46]. However, drought increased C 3 WUE overall, but tended to decrease C 4 WUE (Figure 1).…”
Section: Photosynthetic Pathwayssupporting
confidence: 92%
“…Pode-se inferir que o aumento da produtividade de colmos (TCH), no manejo de cana irrigada por gotejamento (1.797 mm) em comparação com o manejo de cana de sequeiro (1.437 mm), foi causado pela diminuição do estresse hídrico tendo em vista que a ocorrência desse tipo de estresse provoca, segundo alguns autores, redução de trocas gasosas (Farquhar et al, 1989;Inman-Bamber & Smith, 2005); diminuição da área foliar e, consequentemente, do índice de área foliar (Inman-Bamber & Smith, 2005;Smit & Singels, 2006); redução no surgimento de novas folhas e aumento da abscisão foliar (Smit & Singels, 2006) em virtude da elevação da concentração de ácido abscísico na planta (Ghannoum, 2009), que é associado à quantidade de luz absorvida e à fotossíntese total da cana-deaçúcar (Irvine, 1975), reduzindo a produção de fotassimilados (Farquhar et al, 1989;Lopes et al, 1988). Essas características fisiomorfológicas modificadas pelo estresse hídrico são consideradas de grande importância para se obter elevadas produtividades vegetais (Inman-Bamber & Smith, 2005;Ghannoum, 2009).…”
Section: Resultsunclassified
“…Essas características fisiomorfológicas modificadas pelo estresse hídrico são consideradas de grande importância para se obter elevadas produtividades vegetais (Inman-Bamber & Smith, 2005;Ghannoum, 2009). Para as condições de campo deste experimento, a cana-deaçúcar necessitou, em média, de 14,2 mm de água para produzir uma tonelada de colmos (EUA-TCH), (Tabela 1); resultado semelhante a este foi verificado por Foligata (1974) O incremento da produtividade de açúcar (TPH) ocorreu devido ao maior acúmulo de biomassa pela cultura, no manejo Tabela 1.…”
Section: Resultsunclassified
“…Studies concerning the effect of water stress on the photosynthesis by C 4 plants are fewer than for C 3 (Ghannoum 2009), despite their ecological, social and economic relevance. C 4 plants evolved 50-60 million years ago (Jacobs et al 1999;Kellogg 2001) when temperatures were higher by 8-10 ºC and the concentration of CO 2 in the atmosphere was lower than at present.…”
Section: Introductionmentioning
confidence: 99%